1980
DOI: 10.1099/00221287-118-2-529
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Extracellular Protein Secretion by Staphylococcus staphylolyticus

Abstract: The differential rate of extracellular protein formation by Staphylococcus staphylolyticus, the lysostaphin-producing organism, was biphasic with a low rate of exoprotein secretion during exponential growth and an increased rate during the post-exponential phase of growth. After 20 h, when no further exoprotein was secreted, exoprotein accounted for 5% of the total protein in the culture. The secretion of three extracellular enzymes was monitored and found to represent a constant proportion of total exoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
3
21
0
Order By: Relevance
“…This compares very well with p (proteinase)-x (cell density) plots in Coleman (1967), and can be compared to similar plots in other work (Coleman, 1981;Robinson et al, 1980;Abbas-Ali and Coleman 1977). This argument suggests that the simple model presented here can serve as a useful representation of the extracellular production of protein, for that class of organisms which has the switching behaviour described in the introduction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This compares very well with p (proteinase)-x (cell density) plots in Coleman (1967), and can be compared to similar plots in other work (Coleman, 1981;Robinson et al, 1980;Abbas-Ali and Coleman 1977). This argument suggests that the simple model presented here can serve as a useful representation of the extracellular production of protein, for that class of organisms which has the switching behaviour described in the introduction.…”
Section: Discussionsupporting
confidence: 82%
“…A number of different experiments for different organisms yield values in the range 0-025-0-25 mg ml" 1 hr" 1 at bacterial dry weights of about 1 to 6 mg ml" 1 (AbbasAli Coleman 1967Coleman , 1981Coleman, Jakeman & Martin, 1978;Robinson, Keating, & Sloan, 1980;Williams & Wimpenny, 1977). We take k 2~0 -01 mg (protease) mg (bacteria)" 1 hr" 1 .…”
Section: X=y(s*-s) and I V-mentioning
confidence: 99%
“…simulans biovar staphylolyticus secretes pro-endopeptidase (M r 59 K), which is proteolytically processed to endopeptidase (M r 26 K) [5,14,15]. In our studies of extracellular protein production by this organism, we have detected only one proteolytic activity, which is due to sulphydryl protease [7][8][9][10]13]. Zhou et al [16] purified this enzyme and showed that it converted purified proendopeptidase to endopeptidase.…”
Section: Introductionmentioning
confidence: 93%
“…Bacterial growth and enzyme assays S. simulans biovar staphylolyticus was grown in modified lysostaphin production medium [7], and endopeptidase, hexosaminidase and protease activities were determined by standard tube assays as described previously [8,17].…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in OD 660 was measured every 30 min for 3 h. Units of bacteriolytic activity are reported as the linear slope of a plot of OD 660 Proteolytic activities were determined using the insoluble proteolytic substrate azocoll (Calbiochem) as previously described (22,44) with some modifications. The substrate (4 mg/ml) was suspended in 100 mM phosphate buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%